PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBENTUK TEKA-TEKI BERBASIS MACROMEDIA FLASH UNTUK SISWA KELAS V SEKOLAH DASAR - Tuti Septiyani; Galih Istiningsih; Kun Hisnan Hajron (Program Studi PGSD Universitas Flores, 2023)
This research aims to produce interactive media with puzzle media in collaboration with Macromedia Flash. This medium can increase students' enthusiasm for learning and help students in understanding the subject matter. Research is used using research and development methods (Research and Development). This research was conducted in the odd semester of the 2022-2023 school year. The subjects of this study were grade V students of SD Negeri Cacaban 6, Magelang Tengah District, Magelang City. The respondents of this study were 6 students of SD Negeri Cacaban 6. Data analysis in this study used validity tests and student response questionnaires. Macromedia Flash-Based Puzzle Media has been validated by 2 validators, namely expert lecturer validators and class V teacher validators. As a result of the validation that has been carried out, the media showed a score of 97.7% with a category very worthy of use. Student responses to this media showed a percentage of 97.5% obtained from the respondents' questionnaire. Thus, the Macromedia Flash-Based Puzzle media is declared suitable for use for the learning process.